2011
DOI: 10.1080/08870446.2011.531573
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural health-promotion intervention increases fruit and vegetable consumption and physical activity among South African adolescents: a cluster-randomised controlled trial

Abstract: Rates of chronic diseases are high among Black South Africans. Few studies have tested cognitive-behavioral health-promotion interventions to reduce chronic diseases in South Africa. We tested the efficacy of such an intervention among adolescents in a cluster-randomized controlled trial. We randomly selected 9 of 17 matched-pairs of schools and randomized one school in each pair to the cognitive-behavioral health-promotion intervention designed to encourage health-related behaviors and the other to a HIV/STD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(133 citation statements)
references
References 23 publications
1
128
0
4
Order By: Relevance
“…When the computer/internetdelivered advice was administered during class time (n = 7), the PA outcomes were only significant in 28.6% of the studies, compared to 40% of those administered outside of the classroom (n = 5). Psychosocial measures were included in 33 of the studies, 17 of which reported statistically significant differences in measured outcomes, including self-efficacy (Lindgren et al, 2011;Lubans and Sylva, 2006;Murray and Tenenbaum, 2010;Pate et al, 2005;Simon et al, 2008;Taymoori and Lubans, 2008), autonomous motivation (Chatzisarantis and Hagger, 2009), intentions (Chatzisarantis and Hagger, 2009;Hill et al, 2007;Jemmott et al, 2011;Marks et al, 2006;Simon et al, 2008;Tsorbatzoudis, 2005), self-esteem (Neumark-Sztainer et al, 2010), behavioural control (Hill et al, 2007;Tsorbatzoudis, 2005), attitudes (Hill et al, 2007;Jemmott et al, 2011), normative beliefs (Hill et al, 2007), and progression in PA stages of change (Mauriello et al, 2010;Neumark-Sztainer et al, 2003a,b).…”
Section: Efficacy/effectivenessmentioning
confidence: 98%
“…When the computer/internetdelivered advice was administered during class time (n = 7), the PA outcomes were only significant in 28.6% of the studies, compared to 40% of those administered outside of the classroom (n = 5). Psychosocial measures were included in 33 of the studies, 17 of which reported statistically significant differences in measured outcomes, including self-efficacy (Lindgren et al, 2011;Lubans and Sylva, 2006;Murray and Tenenbaum, 2010;Pate et al, 2005;Simon et al, 2008;Taymoori and Lubans, 2008), autonomous motivation (Chatzisarantis and Hagger, 2009), intentions (Chatzisarantis and Hagger, 2009;Hill et al, 2007;Jemmott et al, 2011;Marks et al, 2006;Simon et al, 2008;Tsorbatzoudis, 2005), self-esteem (Neumark-Sztainer et al, 2010), behavioural control (Hill et al, 2007;Tsorbatzoudis, 2005), attitudes (Hill et al, 2007;Jemmott et al, 2011), normative beliefs (Hill et al, 2007), and progression in PA stages of change (Mauriello et al, 2010;Neumark-Sztainer et al, 2003a,b).…”
Section: Efficacy/effectivenessmentioning
confidence: 98%
“…20,29 Three primary school interventions apart from HK have been evaluated in South Africa. [30][31][32] One of these was undertaken by Jacobs et al 30 in Grade 4 learners in the Western Cape, where an existing and ongoing intervention was evaluated. Four intervention and five control schools were randomly selected from two school districts.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although some school-based interventions have shown behavior change in similar age groups, 2,5,6,30,32,35 the low intensity of the intervention, the lack of significant changes in the school environment and the poor involvement of parents as described earlier 20 could have hindered children from making changes in their eating behavior. The improvement of nutrition knowledge is, however, an important achievement, and although nutrition knowledge on its own is not sufficient for behavior change, Worsley, 36 after a review of the literature, suggests that nutrition knowledge "may play a small but pivotal role in the adoption of healthier food habits.…”
mentioning
confidence: 99%
“…This might be connected to the outcome expectations and expectancies. As stated by Jemmott et al, 30 attitude is determined by beliefs about the consequences of performing behavior. Experimental group 1 (the CCBNEd program) seemed to have higher outcome expectations and expectancies regarding the benefits of F&V consumption.…”
Section: Discussionmentioning
confidence: 99%